Application of dynamic magnetic resonance imaging information technology in adjuvant chemotherapy for breast cancer - Caixian Yang; Hongguang Zhao (Elsevier, 2020)
In order to study the application of dynamic magnetic resonance imaging information technology in breast cancer adjuvant chemotherapy, female patients diagnosed with breast cancer in The People's Hospital of Shanxi Province are selected as research objects. Dynamic enhanced magnetic resonance imaging scans are performed to compare pathological changes by hematoxylin and eosin staining. The dynamic NMR morphological changes are used to evaluate the efficacy of neoadjuvant chemotherapy. Semi-quantitative analysis is used to compare the TIC types of lesions, and the changes in quantitative analysis parameters are used to evaluate the efficacy. The results show that in the dynamic magnetic resonance imaging technique, the effective group (RECIST standard is CR and PR) has statistically significant changes in the quantitative analysis parameters Ktrans and Kep before and after neoadjuvant chemotherapy. Ktrans and Kep are used in neoadjuvant chemotherapy for breast cancer. The assessment is consistent with the morphological RECIST criteria assessment and can be used for qualitative diagnosis of breast tumors.